Probiotic-Based Bacteriocin: Immunity Supplementation Against Viruses. An Updated Review - Umair, Muhammad; Jabbar, Saqib; Zhaoxin, Lu; Jianhao, Zhang; Abid, Muhammad; Khan, Kashif-Ur R.; Korma, Sameh A.; Alghamdi, Mashail A.; El-Saadony, Mohamed T.; Abd El-Hack, Mohamed E.; Cacciotti, Ilaria; AbuQamar, Synan F.; et al. (Frontiers in Microbiology, 2022)
Viral infections appear to cause significant life-threatening diseases worldwide. These diseases are expected to increase in recent years due to challenging contextual factors such as environmental changes, enlarged mobility for people and products, rapid demographic changes, and the outbreaks of novel virus species such as COVID-19. Parallel to these external causes, the internal factors that influence viral immunity have been gaining attention to cob such novel viral outbreaks. The gastrointestinal microbiome (GIM), particularly the present probiotics, is recognized as an important factor in the host immune system, serving as a host protection and immunity mechanisms regulator. Probiotics and their metabolism, including bacteriocin, have been shown to have a variety of health advantages. They can play as antagonists against enteric pathogens and immunobiotics, thus avoiding viral infections. Furthermore, disrupting the GIM/host immune system homeostasis can have a detrimental effect on viral immunity. However, the interaction between the bacteriocin and infectious viruses, particularly COVID-19, through the improvement of the host immunity and physiology is complicated and has not been studied yet, even if several evidences have demonstrated that the bacteriocin may influence viral disease outcomes. Some alternative therapies were previously selected for viral infections, including siRNA treatment that can trigger the gene silencing through sequence-specific cleavage of perfectly complementary RNA messenger (mRNA). Nevertheless, the complicated transmission to the affected sites and the siRNA defense from nuclease digestion make the clinical trials more challenging. Bacteriocins, as a metabolite of probiotics, are well documented for their bio-functional properties and action mode to treat bacterial and fungal infections. Though, a few studies summarize the role of bacteriocin derived from probiotics in fighting viral infections. This review aims to lay out a road map for future research on bacteriocin for the viral infection’s treatment, on the basis of previous research efforts.